Positive Association between ANKRD55 Polymorphism 7731626 and Dermatomyositis/Polymyositis with Interstitial Lung Disease in Chinese Han Population. (2nd April 2017) - Li, Liubing; Chen, Si; Wen, Xiaoting; Wang, Qian; Lv, Guanting; Li, Jing; Yang, Funing; Zhang, Fengchun; Li, Yongzhe
Abstract : Single nucleotide polymorphisms (SNPs) in TNFSF4 and ANKRD55 genes have been shown to be associated with several autoimmune diseases, although whether these genes are susceptibility genes for dermatomyositis/polymyositis (DM/PM) has, to date, not been reported. This study aimed to investigate the potential associations of these SNPs with DM/PM in a Chinese Han population. Five SNPs in TNFSF4 (rs2205960, rs844644, and rs844648) and ANKRD55 (rs6859219, rs7731626) genes were genotyped using the SequenomMassArray system in 2297 Chinese individuals. In total, 1017 DM/PM patients and 1280 gender-matched healthy controls were genotyped. No significant associations were observed in DM/PM patients for the five SNPs analyzed. The association between SNPs and interstitial lung disease (ILD) was also investigated. Both DM-ILD (P c = 0.030, OR = 0.65, 95% CI: 0.47–0.88) and DM/PM-ILD (P c = 0.015, OR = 0.67, 95% CI: 0.51–0.87) exhibited a significant association with the rs7731626-A allele. Rs7731626-A was less frequently found in DM-ILD and DM/PM-ILD patients compared with healthy controls. This is the first study to demonstrate a positive association between ANKRD55 polymorphism and DM-ILD and DM/PM-ILD. A decreased frequency of rs7731626-A in DM-ILD and DM/PM-ILD patients suggests that the A variant may be protective against DM/PM-ILD.